2015
DOI: 10.1128/aem.02805-14
|View full text |Cite
|
Sign up to set email alerts
|

MomL, a Novel Marine-Derived N -Acyl Homoserine Lactonase from Muricauda olearia

Abstract: bGram-negative bacteria use N-acyl homoserine lactones (AHLs) as quorum sensing (QS) signaling molecules for interspecies communication, and AHL-dependent QS is related with virulence factor production in many bacterial pathogens. Quorum quenching, the enzymatic degradation of the signaling molecule, would attenuate virulence rather than kill the pathogens, and thereby reduce the potential for evolution of drug resistance. In a previous study, we showed that Muricauda olearia Th120, belonging to the class Flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(136 citation statements)
references
References 44 publications
5
129
1
Order By: Relevance
“…The denaturation and refolding process strongly affected the thermo resistance of the enzyme. Residual enzymatic activity was found in the purified, full sequence Aii20J after a treatment of 80°C for 10 min, but only when reconstituted in the presence of metallic ions, which indicates that the presence of metal ions is beneficial for the correct folding and catalytic activity of the protein, as described previously for other metallohydrolases (Cao et al 2012;Chen et al 2010;Momb et al 2008;Tang et al 2015;Wang et al 2012) and confirms that correct folding is a key factor in the thermostability of the denaturized enzyme. Activity was still present in the purified enzyme after a treatment at 60°C during 10 min but was significantly reduced in comparison with the untreated enzyme (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…The denaturation and refolding process strongly affected the thermo resistance of the enzyme. Residual enzymatic activity was found in the purified, full sequence Aii20J after a treatment of 80°C for 10 min, but only when reconstituted in the presence of metallic ions, which indicates that the presence of metal ions is beneficial for the correct folding and catalytic activity of the protein, as described previously for other metallohydrolases (Cao et al 2012;Chen et al 2010;Momb et al 2008;Tang et al 2015;Wang et al 2012) and confirms that correct folding is a key factor in the thermostability of the denaturized enzyme. Activity was still present in the purified enzyme after a treatment at 60°C during 10 min but was significantly reduced in comparison with the untreated enzyme (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…The resuspended cells were lysed using Sonics Vibracell TM sonicator (30% amplitude for 3 minutes at alternating intervals of 9 seconds) and supernatant and cell content were collected after centrifugation at 10,000 rpm for 10 min at 4°C. 20μl of culture supernatant, supernatant after sonication or cell pellet after sonication were assayed individually for AHL degradation by mixing with 80μl of 25μM C6HSL and incubating at 30°C for 2 hours under static conditions followed by the biosensor assay described above [25]. Reaction mixture containing whole cell of Lysinibacillus sp.…”
Section: Methodsmentioning
confidence: 99%
“…amyloliquefaciens , Geobacillus sp.) [1318]; and also in the Actinobacteria ( Arthrobacter sp ., Microbacterium testaceum , Rhodococcus erythropolis ) [1921]; Proteobacteria ( Agrobacterium , Ochrobactrum sp., Klebsiella pneumoniae ) [22, 23, 19] and Bacteroidetes) ( Chryseobacterium sp., Muricauda olearia ) [24, 25]. The AHL lactonases produced by all these bacteria belong to the metallo- β-lactamase, phosphotriesterase (PTE) and α/β hydrolase-fold families of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing and bioinformatic results demonstrate that the genome contains a gene encoding AHL lactonase named MomL. MomL consists of 294 amino acids with a molecular weight of approximately 38.4 KDa [29]. MomL belongs to the metallo-β-lactamase family, and the homolog exhibits a 24.5% similarity with AiiA.…”
Section: Ahl Lactonasementioning
confidence: 99%
“…In vitro enzyme assays indicated that MomL possesses high activity and broad substrate selectivity. Kinetic results indicated MomL had 10-fold increased C6-HSL (C6-homoserine lactones) degrading activity compared with AiiA protein [29]. …”
Section: Ahl Lactonasementioning
confidence: 99%